I-Deals: Idiosyncratic Terms in Employment Relationships - Rousseau, Denise M.; Ho, Violet T.; Greenberg, Jerald (Academy of Management Review, 2006)
Idiosyncratic employment arrangements (i-deals) stand to benefit the individual employee as well as his or her employer. However, unless certain conditions apply, coworkers may respond negatively to these arrangements. We distinguish functional i-deals from their dysfunctional counterparts and highlight evidence of i-deals in previous organizational research. We develop propositions specifying both how ideals are formed and how they impact workers and coworkers. Finally, we outline the implications i-deals have for research and for managing contemporary employment relationships.